The EU own resources system: Reform needs and options - Margit Schratzenstaller (Intereconomics, 2013)
The most prominent and debated issues in the negotiations on the next Multiannual Financial Framework for the EU for the period 2014-2020 were the overall budget volume, the structure of expenditures and the continuation of the rebates for (some) net contributor countries. However, the system of the EU's own resources was hardly addressed in the negotiations, although it is one of the most important obstacles to reform. This article reviews the most important deficits of the current system of own resources and assesses the most substantial reform proposal which has been advocated for years by the European Commission, namely to finance part of the EU budget through EU taxes.
Keywords: 330; EU-Haushalt; Reform; EU-Staaten